Neutrophil to Lymphocyte Ratio in Epilepsy: A Systematic Review - Samaneh Hosseini; Amir Mohammad Eghbalnejad Mofrad; Peyman Mokarian; Shima Nourigheimasi; Amir Azarhomayoun; Shokoufeh Khanzadeh; Saba Habibzadeh; Arshin Ghaedi (Mediators of Inflammation)
This study was conducted to summarize the results of studies investigating the role of neutrophil to lymphocyte ratio (NLR) in epilepsy. The search was conducted on PubMed, Scopus, and Web of Science up to December 25, 2021. Finally, a total of seven studies were included in the review. The NLR in patients who were in the acute phase was higher than that of healthy. NLR in the patients who were in either acute or subacute phase was higher than in healthy controls. A significant difference in NLR levels between the acute and subacute phases was also noted. Epilepsy is one of the most important neurological diseases in the world, and millions of people around the world suffer from it, and a cheap and fast biomarker is needed for it. The interesting thing is that inflammation plays a role in epilepsy, and elevated NLR value can be a good biomarker of inflammation and, as a result, for epilepsy.